DASAR-DASAR RESOLUSI KONFLIK DALAM PENDIDIKAN ISLAM - Abdullah Safei (LP2M JAMIAT KHEIR, 2023)
Based on the conditions and reality of the dynamics of social life of society, religion is used as a justification reason, then religion, which certainly teaches peace and tranquility, will no longer feel relevant to be used as a guideline. However, if religious teachings are applied properly and also understood correctly and not ruled out, then religion in this case Islam which is guided by the holy book of the Qur'an must be relevant and can provide solutions to every problem that exists. Questioning the relevance of religion, in this case Islam with objective situations and conditions in people's social life tends to be unstable due to the vulnerability of vertical or horizontal conflicts is very interesting to watch, especially if the discussion comes to a resolution with peace in the perspective of the Qur'an. Indeed, the teachings of Islam, as embodied in the holy book of the Qur'an, teach that humans create an atmosphere of harmony, peace, security, and peace in life. Islam strongly dislikes anarchist behavior and prolonged conflict. Islamic leaders, such as ulama, kyai, ustadz or muballigh always remind the Islamic community to spread peace in human life. Therefore, if there is a different situation in the followers of Islam, then something must be wrong. The occurrence of disharmony in a society that embraces religion, because religious teachings are not practiced properly.